THE CIRC TECHNIQUE AND LEARNING MOTIVATION FOR IMPROVING STUDENTS’ READING COMPREHENSION SKILLS - Eti Mulyawati (INFERENCE: Journal of English Language Teaching, 2021)
This research aims to know the effect of the CIRC technique and learning motivation on reading comprehension skills at State Senior High School in Pandeglang Regency. The research method which is conducted is an experimental study with two-way ANOVA. The samples were 30 students of SMAN 6 and 30 students of SMAN 8 taken by cluster. The technique of collecting data on each variable was acquired from the test. The data was analyzed by using a two-way analysis of variance (ANOVA 2x2). The research results show no interactive effects of teaching technique and learning motivation toward reading comprehension skill State Senior High School in Pandeglang Regency with the value of sig 0.01<0.05 and F0 =5.872.Keywords: teaching technique, learning motivation, and reading comprehension skill